1994
DOI: 10.1128/iai.62.3.874-879.1994
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-specific T cells in human peripheral blood after oral immunization with an inactivated enterotoxigenic Escherichia coli vaccine

Abstract: We have examined whether oral immunization of adult Swedish volunteers with a prototype enterotoxigenic Escherichia coli vaccine would induce antigen-specific T-cell responses in blood. Volunteers were given one to three doses of the whole-cell component of the vaccine, which consisted of formalin-inactivated bacteria expressing the fimbrial colonization factor antigens I and II. Following immunization, in vitro stimulation of blood mononuclear cells with the colonization factor antigens resulted in modest pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…Together, these cytokines may play a significant role in a protective immune response against ETEC. Although IFN-γ secretion has been documented following ETEC vaccination [ 35 ], we did not identify a significant difference in IFN-γ production between Resistant and Susceptible volunteers. It is important to note that measurement of IFN-γ secretion by Wenneras et al was by ELISPOT and ELISA which cannot distinguish among the specific cell subset(s) producing the cytokine.…”
Section: Discussioncontrasting
confidence: 89%
“…Together, these cytokines may play a significant role in a protective immune response against ETEC. Although IFN-γ secretion has been documented following ETEC vaccination [ 35 ], we did not identify a significant difference in IFN-γ production between Resistant and Susceptible volunteers. It is important to note that measurement of IFN-γ secretion by Wenneras et al was by ELISPOT and ELISA which cannot distinguish among the specific cell subset(s) producing the cytokine.…”
Section: Discussioncontrasting
confidence: 89%
“…Although the results of several studies have indicated that specific sIgA and IgA in serum may be good markers for anti-Campylobacter immunity (10,12), the data presented here tend to indicate that they alone may not be sufficient to ensure protection. These antibodies may work in tandem with other cell-mediated effector mechanisms (22) and/or other soluble mediators such as cytokines (14,17) to mediate the protection that is afforded by immunization with these vaccine formulations. The priming and subsequent development of intestinal antibacterial immune responses appear to be critically dependent on the amount of antigen initially delivered to the gut-associated lymphoid tissue (6).…”
Section: Vol 63 1995 Notesmentioning
confidence: 99%
“…In general, inactivated bacterial whole cells offer several advantages as candidate enteric vaccines in that they are potentially inexpensive to produce, are generally safe, and when preserved properly, serve as naturally occurring microparticles which may function to facilitate the delivery and presentation of vaccine antigens to mucosal lymphoid tissue (19). At present, inactivated whole-cell vaccines, like those for cholera or disease caused by enterotoxigenic E. coli, must be given orally in large doses to be effective (8,16,21,22). On the basis of our findings, this drawback could be overcome by the coadministration of LT with these vaccines.…”
Section: Vol 63 1995 Notesmentioning
confidence: 99%
“…The elaboration of an ETEC vaccine has been deemed to be of high priority because ETEC infections lead to high mortality and morbidity levels among children in developing countries. An inactivated ETEC vaccine consisting of a combination of CTB and formalin-inactivated ETEC bacteria expressing the most-prevalent CFAs has been tested on Swedish (1,2,13,33,34) as well as Egyptian volunteers (26,27). The vaccine is given orally because elicitation of mucosal immune responses in the intestine has been considered to be of prime importance for protection.…”
mentioning
confidence: 99%